Direito e Angústia em Søren Kierkegaard: diálogos com o tempo presente - Castanha, Ruth Faria da Costa (2018)
The present master’s dissertation is the result of the anguish caused by the Kierkegaardian thought regarding the law and reality of the legal world. The chosen subject speaks in a transversal way with several law trades, mainly with the law philosophy, in which the debate is centralized; easily gets through the Legal Sociology, Psychology and Religious Studies. However, with kindness, invites the Theology to take the floor and to speak side by side with the Law. The theme, from the point of view proposed, wasn’t much explored in the scientific field, that’s why stands out its importance on the comprehension of the anguish which bothers and moves that one that seeks for the correct interpretation of the law. For the sake of debate, we have appropriated of the anguish concept contained in the oeuvre from the Danish author Sören Kierkegaard of various legal aspects concerning what would be the law and its subject